2015
DOI: 10.1371/journal.pone.0139892
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Different Repetitive Transcranial Magnetic Stimulation (rTMS) Protocols on Cortical Gene Expression in a Rat Model of Cerebral Ischemic-Reperfusion Injury

Abstract: Although repetitive Transcranial Magnetic Stimulation (rTMS) in treatment of stroke in humans has been explored over the past decade the data remain controversial in terms of optimal stimulation parameters and the mechanisms of rTMS long-term effects. This study aimed to explore the potential of different rTMS protocols to induce changes in gene expression in rat cortices after acute ischemic-reperfusion brain injury. The stroke was induced by middle cerebral artery occlusion (MCAO) with subsequent reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 87 publications
(108 reference statements)
3
62
0
Order By: Relevance
“…In a model of experimental stroke, induced by transient 90 min of middle cerebral artery occlusion, rats were exposed 4 days later to a 1 Hz, 5 Hz, and continuous or intermittent theta-burst rTMS protocol. At the end of the stimulation period (Ljubisavljevic et al, 2015 ), only intermittent theta-burst rTMS protocol induced differential up-regulation of 52 genes in rat cortices, these genes being involved in angiogenesis, inflammation, neuroprotection and cellular repair, all these mechanisms promoting recovery (Nih et al, 2012 ; Poittevin et al, 2013 ). In the same model, but with a different rTMS protocol using high-frequency stimulation applied 1 h after the onset of ischemia, neuroprotective effect was evidenced via anti-apoptosis of the cells located at the margin of the infarct (Gao et al, 2010 ).…”
Section: Experimental Datamentioning
confidence: 99%
“…In a model of experimental stroke, induced by transient 90 min of middle cerebral artery occlusion, rats were exposed 4 days later to a 1 Hz, 5 Hz, and continuous or intermittent theta-burst rTMS protocol. At the end of the stimulation period (Ljubisavljevic et al, 2015 ), only intermittent theta-burst rTMS protocol induced differential up-regulation of 52 genes in rat cortices, these genes being involved in angiogenesis, inflammation, neuroprotection and cellular repair, all these mechanisms promoting recovery (Nih et al, 2012 ; Poittevin et al, 2013 ). In the same model, but with a different rTMS protocol using high-frequency stimulation applied 1 h after the onset of ischemia, neuroprotective effect was evidenced via anti-apoptosis of the cells located at the margin of the infarct (Gao et al, 2010 ).…”
Section: Experimental Datamentioning
confidence: 99%
“…Furthermonre, studies reporting increased neurogenesis with increased neural stem cell progenitor proliferation, were often performed in healthy rodent models in the absence of neuroinflammation [25,26,62]. Additionally, induced neuroregeneration upon rTMS therapy was mostly found in adult rodent models [23,25,62]. These results might therefore differ from our infant model, where the rate of endogenous neurogenesis is already considerably high [11].…”
Section: Discussionmentioning
confidence: 86%
“…We applied a comparably short stimulation protocol with four stimulation trains per day on 2 consecutive days, which represents a setup that showed beneficial effect in treatment of human neglect patients after stroke [5759]. This is in contrast to stimulation for up to 60 days in studies with reported positive effect on neurogenesis [23,60,61]. In addition, we isolated brain tissues 24 hours after the last stimulation train to assess short-term effects of TBS, compared to some studies with significant longer poststimulation assessment [53].…”
Section: Discussionmentioning
confidence: 99%
“…To solve these problems, we designed the restraint devices to improve the delivery of rTMS and replicated some previous conclusions in humans or animals (Maeda et al, 2000;Muller et al, 2014) to confirm the effectiveness. As compared to previous restraint methods, the methods appeared to more practical, especially making the delivery of rTMS more convenient (Hesselberg et al, 2016;Lim et al, 2014;Ljubisavljevic et al, 2015;Sasso et al, 2016). However, their usefulness and effectiveness need to be verified by more researchers in the future.…”
Section: The Use Verification and Discussion For Restraint Devicesmentioning
confidence: 99%
“…Therefore, it is necessary to take some measures to restrain the animals. In previous literature, investigators used the anesthesiology method (Sasso et al, ; Sykes et al, ), or by hand (Hesselberg, Wegener, & Buchholtz, ; Lim, Lee, Yoo, & Kwon, ; Sasso et al, ), or cloth, bag and straps (Ljubisavljevic et al, ); Tang et al, ), or some undefined devices (Guo et al, ). In animals, rTMS is often used 1–2 times each day (for minutes to tens of minutes each time), lasts for a few of days or tens of days (Fleischmann & Hirschmann, ; Guo et al, ; Ji et al, ).…”
Section: Introductionmentioning
confidence: 99%